\(ng^#\)-Closed Sets In An Ideal Nano Topological Space - Devi, S.; Rameshpandi, M.; David, S. Antony (Communications in Mathematics and Applications, 2021)
In this paper, we propose to introduce the new classes of \(ng^#\)-closed sets, \(nI_g^#\)-closed sets, \(nα g^#\)-closed sets and completely nano codense in ideal an nano topological space. Also, we studied the \(nI_g^#\)-closed sets and establish their various characteristic properties.